2011
DOI: 10.1186/ar3474
|View full text |Cite
|
Sign up to set email alerts
|

Increase in IL-21 producing T-cells in patients with systemic lupus erythematosus

Abstract: IntroductionSystemic lupus erythematosus (SLE) is an autoimmune disease accompanied by a disturbed T-cell balance skewed towards effector T-cells, in particular Th17-cells. The novel cytokine interleukin-21 (IL-21) is suggested to be crucial for triggering T-cell responses towards IL-17 producing cells. Thus, we aimed to investigate the ability of T-cells to produce IL-21 and IL-17 in SLE patients.MethodsPeripheral blood of 34 SLE patients and 18 healthy controls (HC) was stimulated with phorbol myristate acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 27 publications
7
82
2
Order By: Relevance
“…Recently, it has been demonstrated that the combination of the pro-inflammatory interleukin-21 (IL-21) and B cell receptor (BCR) stimulation enables B cells to produce and secrete the active form of the cytotoxic serine protease granzyme B (GrB), that, even if it is not accompanied by the production of perforin, as in Natural Killer (NK) and Cytotoxic T lymphocytes, plays a critical role in early anti-viral immune responses, in the regulation of autoimmune mechanisms and in cancer immunosurveillance . Moreover, recent studies have revealed an increase of IL-21 levels in the elderly (Agrawal et al, 2012) and in SLE patients (Dolff et al, 2011) in which we and other groups (Colonna-Romano et al, 2009;Sanz et al, 2008;Wei et al, 2007) have shown the increase of DN B cell population. In order to evaluate whether DN B cells are also involved in IL-21-mediated immune response, we tested the capacity of these cells to produce GrB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the combination of the pro-inflammatory interleukin-21 (IL-21) and B cell receptor (BCR) stimulation enables B cells to produce and secrete the active form of the cytotoxic serine protease granzyme B (GrB), that, even if it is not accompanied by the production of perforin, as in Natural Killer (NK) and Cytotoxic T lymphocytes, plays a critical role in early anti-viral immune responses, in the regulation of autoimmune mechanisms and in cancer immunosurveillance . Moreover, recent studies have revealed an increase of IL-21 levels in the elderly (Agrawal et al, 2012) and in SLE patients (Dolff et al, 2011) in which we and other groups (Colonna-Romano et al, 2009;Sanz et al, 2008;Wei et al, 2007) have shown the increase of DN B cell population. In order to evaluate whether DN B cells are also involved in IL-21-mediated immune response, we tested the capacity of these cells to produce GrB.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL-21 levels were found in lupus-prone BXSB.Yaa mice, and autoimmune features were attenuated in BXSB.Yaa and MRL-Fas lpr mice following genetic deletion of IL-21R or IL-21 blockade (20)(21)(22)(23). In patients with lupus, an association between polymorphisms in the IL-21 and IL-21R gene and disease susceptibility was reported, along with increased circulating and intracellular levels of IL-21 (24)(25)(26)(27)(28). Thus, IL-21 is an attractive candidate for therapeutic targeting in autoimmune diseases, including SLE.…”
Section: Nterleukin-21 Is a Member Of The Type I Cytokine Family Wimentioning
confidence: 99%
“…In the mouse, autocrine IL-21 signaling has been proposed to promote Th17 differentiation (36,(41)(42)(43), and consistently, human patients with defective IL-21R signaling lack Th17 cells (44). However, although IL-21 can promote autoimmune diseases such as systemic lupus erythematosus (45,46) or type 1 diabetes (47) by its effect on B cells (48) and dendritic cells (DCs) (49), respectively, inconsistent results have been published on the role of IL-21 in Th17 cell differentiation and Th17-driven experimental autoimmune encephalomyelitis (41,50,51). Interest-ingly, the addition of exogenous TGF-b and IL-21 was reported to induce Th17 differentiation of human naive T cells (8).…”
Section: Ytokines Regulate the Differentiation Of Uncommitted Naivementioning
confidence: 99%